PERANCANGAN MASKOT âPLANKTOON FINGERBOARDâ SEBAGAI UPAYA MENINGKATKAN BRAND LOYALTY - Mahendra, Yoda Aji; Bahruddin, Muh; Sutrisna, Andika Agung (Jurnal Art Nouveau, 2015)
Abstract: Planktoon known as Planktoon Fingerboard, is a company engaged in the field of life style product that has specifications field in fingerboard. Fingerboard is a skateboardâs miniature that made in the same detail as the size of the original skateboard, but it has smaller size to make it more comfortable in play using the fingers. Planktoon founded in 2009, exactly 23 October 2009, from there began the management system created for branding fingerboard with pride. Planktoon brand name, logo and stationery set has been made yet before, but Planktoon has not had a mascot, just like brand competitors from Planktoon. Therefore in order to improve the image of Planktoon. Mascot hopefully can educate consumers and increase Planktoonâs brand image. Designing qualitative method with interviews, observation, and existing studies to find a formula for the design concepts underlying the design of the mascot, the data analysis found a variety of unique and how branding brand with mascots that have not been known by the public, so consumers are not only given a new product continuously without any explanation interesting, with mascot be easier for consumers to understand about Planktoon. After analyzing the concepts found and a name for the mascot design PlanktoonÂ the